BMPR2 mutations and response to inhaled or parenteral prostanoids: a case series. (1st December 2021) - Scelsi, Laura; Greco, Alessandra; Acquaro, Mauro; Olivieri, Carla; Sobrero, Matteo; Turco, Annalisa; Cappelletti, Donata; Visconti, Luigi Oltrona; Ghio, Stefano
Abstract : Whether mutations in the BMPR2 gene may influence the response to PAH‐specific therapies has not yet been investigated. In this study, in 13 idiopathic, heritable or anorexigen‐associated PAH patients, in whom treatment escalation was performed by adding a prostanoid, a greater haemodynamic improvement was observed in BMPR2‐negative than in BMPR2‐positive patients.